2018
DOI: 10.1111/bju.14228
|View full text |Cite
|
Sign up to set email alerts
|

Localised prostate cancer in elderly men aged 80–89 years, findings from a population‐based registry

Abstract: The proportion of prostate cancer deaths was similar in both groups. These findings support carefully selected individualised management of elderly patients diagnosed with localised prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 27 publications
2
12
0
1
Order By: Relevance
“…The importance of learning DRE in contemporary medical practice, which has seen the advent of bowel cancer screening and the use of MRI to detect prostate cancer has been debated. Recent studies have shown, however, that older men who are not PSA screening candidates are being diagnosed with localized prostate cancer and subsequently may die from the disease . DRE is important in detecting these high‐risk individuals in addition to detecting prostate cancer in men with normal PSA levels but an abnormal DRE, which is estimated at 11% in a prostate cancer screening trial .…”
Section: Discussionmentioning
confidence: 99%
“…The importance of learning DRE in contemporary medical practice, which has seen the advent of bowel cancer screening and the use of MRI to detect prostate cancer has been debated. Recent studies have shown, however, that older men who are not PSA screening candidates are being diagnosed with localized prostate cancer and subsequently may die from the disease . DRE is important in detecting these high‐risk individuals in addition to detecting prostate cancer in men with normal PSA levels but an abnormal DRE, which is estimated at 11% in a prostate cancer screening trial .…”
Section: Discussionmentioning
confidence: 99%
“…We continue to use the transrectal approach for some repeat biopsies, for tissue diagnosis in men with suspected metastatic prostate cancer, and for those in whom sedation is preferred to general anaesthesia. Registry data suggest selected octogenarians may benefit from prostate cancer treatment, which also raises the ongoing need to evaluate the safety of TRUS‐guided biopsy . Our cohort represents the first Australian operative cohort to be tested for ESBL prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, a multivariable Cox proportional hazard model was used for analyses of OM and CSM after adjusting race, age, marital status, Gleason Score (GS), and prostate specific antigen (PSA). 13 Thirdly, in consideration of baseline characteristics affecting the option of using different treatment methods, propensity score matching (PSM) (ratio 1:1, with a caliper set of 0.05) was performed to ensure that both the RT group and the RP group had similar baseline characteristics with the use of logistic regression to adjust for between-group differences. 14 The matching was conducted based on nearest-neighbor matching principle.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, a multivariable Cox proportional hazard model was used for analyses of OM and CSM after adjusting race, age, marital status, Gleason Score (GS), and prostate specific antigen (PSA) …”
Section: Methodsmentioning
confidence: 99%